Identifica????o e classifica????o de stakeholders em clubes brasileiros de futebol profissional - Pajanian, Fl??vio (2015)
This research aimed to investigate how leaders of Brazilian professional football clubs identify and classify its stakeholders, according to the attributes of power, legitimacy and urgency. The theoretical framework was based on the stakeholder theory, developed by Freeman (1984) and other researchers. For this objective to be achieved, a model for the identification and classification of stakeholders proposed by Mitchell et al. (1997) and operated by Almeida et al. (2000), based on the attributes of power, legitimacy and urgency, was applied. An exploratory and descriptive investigation of mixed method was performed, with leaders of two professional football clubs and operated at two different times, using a pre-established script and a questionnaire. The results obtained from this investigation confirm the two prepared propositions, that the urgency perceived by leaders in meeting the demands of a stakeholder is high when its legitimacy is high and that the most salient stakeholders for the leaders will be those with high legitimacy. It is expected that the obtained results can be used as a reference for leaders of these and other similar entities with respect to its relations with its stakeholders, and also as a starting point for future studies in sport management.